Distributed Smart City Services for Urban Ecosystems - Calderoni, Luca <1982> (Alma Mater Studiorum - Università di Bologna, 2015)
A Smart City is a high-performance urban context, where citizens live independently and are more aware of the surrounding opportunities, thanks to forward-looking development of economy politics, governance, mobility and environment. ICT infrastructures play a key-role in this new research field being also a mean for society to allow new ideas to prosper and new, more efficient approaches to be developed. The aim of this work is to research and develop novel solutions, here called smart services, in order to solve several upcoming problems and known issues in urban areas and more in general in the modern society context. A specific focus is posed on smart governance and on privacy issues which have been arisen in the cellular age.